2020
DOI: 10.1016/j.jpeds.2020.05.048
|View full text |Cite
|
Sign up to set email alerts
|

Hand Function at 18-22 Months Is Associated with School-Age Manual Dexterity and Motor Performance in Children Born Extremely Preterm

Abstract: Objectives: To determine associations between 18-22 month (early) hand function and scores on the Movement Assessment Battery for Children, 2 nd edition (MABC) at 6-7 years of age (schoolage) in extremely preterm children. Study design:Prospective multi-center cohort of 313 extremely preterm children with early hand function assessment and school-age MABC testing. Early hand function was compared with 'definite deficits' (MABC <5 th percentile) and MABC standard scores. Early hand function was categorized as '… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
6
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 7 publications
(6 citation statements)
references
References 37 publications
0
6
0
Order By: Relevance
“…Only 1 study explored behavioral outcomes up to 3 years after WMI, and 3 explored speech and language outcomes. 21 , 33 , 38 , 49 Lean 2019 and Sarkar 2018 both reported a higher crude risk of language impairment after WMI. Lean 2019 reported a higher crude risk after IVH grade 3 to 4 or posthemorrhagic hydrocephalus or cPVL OR 2.53, which did not persist on adjusting for confounders.…”
Section: Resultsmentioning
confidence: 98%
“…Only 1 study explored behavioral outcomes up to 3 years after WMI, and 3 explored speech and language outcomes. 21 , 33 , 38 , 49 Lean 2019 and Sarkar 2018 both reported a higher crude risk of language impairment after WMI. Lean 2019 reported a higher crude risk after IVH grade 3 to 4 or posthemorrhagic hydrocephalus or cPVL OR 2.53, which did not persist on adjusting for confounders.…”
Section: Resultsmentioning
confidence: 98%
“…Second, in GEE analysis that included a set of the most discriminating readiness measures from each of the five domains as predictors of group membership, motor ability discriminated the groups independently of other measures of readiness. These results underscore motor skills as a critical domain in assessment of readiness [4,10,63,64], and suggest that, at least for females, some socioemotional aspects of school readiness may be affected independently of their cognitive competencies.…”
Section: Discussionmentioning
confidence: 73%
“…Whether this can this be accomplished during mostly non-standardized telehealth visits should be explored in the future. Additionally, specific assessments for, e.g., hand function deficits which are associated with school-age motor performance [15], cannot be performed in a telemedicine setting, hence, it seems that while telehealth offers new solutions, it really cannot replace the need for an actual patient encounter to provide the best care to high-risk premature infants.…”
Section: Discussionmentioning
confidence: 99%
“…Lastly, we attempted to obtain data from the Canadian neonatal network, which comprises a total of 10 provinces, by participating in sites by sharing a link to this survey with Canadian neonatal network coordinators [16,17], but we received responses from only five sites. A recent Canadian study by Albaghli et al [15] showed that care in Canada became more consistent after the formation of the Canadian Neonatal Follow-up Network (CNFUN) in 2010, with >90% of sites now providing Bayley-III at 18 months assessment. Although the data were specific to the pre-pandemic era, it will be interesting to see more extensive reporting from CNFUN on the impact and adaptations of their clinics due to the COVID-19 pandemic.…”
Section: Discussionmentioning
confidence: 99%